Perto do fim : os desfechos dos personagens gays no cinema brasileiro - Santos, Jônatas Breno Silva (2019)
This research aims to analyze the narrative outcomes of male homosexual characters in national films, in order to verify which destinations are conferred on them in the narratives along the trajectory of Brazilian cinema. Thus, based on the research undertaken by Moreno (2002) in his book “A personagem homossexual no cinema brasileiro” and a step of own data collection, a Content Analysis was applied in a representative corpus of 61 Brazilian films, located between 1923 and 2017. Therefore, it is a longitudinal investigation of a quantitative and qualitative characteristic, theoretically based on the fields of Cultural Studies, Gender Studies and Queer Theory, that brings the effort to analyze this communicational object and provide a pertinent social discussion regarding the theme. Thus, we compose an overview of the outcomes given to gay characters in Brazilian film narratives, unveiling and problematizing the final treatment that has been given to these identities in the national cinema.